1993
DOI: 10.1300/j013v20n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Psychobiological Stressors Among HIV-Positive Women

Abstract: This research describes major stressors in the lives of women who have been infected with the human immunodeficiency virus (HIV). Thirty-one HIV antibody positive (HIV+) women infected primarily through heterosexual contact participated in a two hour semi-structured interview detailing the circumstances, context, and consequences of all stressful life events and difficulties experienced within the preceding six months. Qualitative methods of data analyses were utilized (Miles & Huberman, 1984). HIV-related lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 12 publications
1
59
0
Order By: Relevance
“…Consistent with prior studies (Murphy et al, 1999;Armistead et al, 2001;Murphy et al, 2001), a relatively small number of children in the current analyses knew of their mother's HIV/AIDS. A mother's disclosure of any chronic or life-threatening illness to her child is often accompanied by some level of hesitation or worry regarding the child's reaction (Semple et al, 1993;Tompkins et al, 1999); however, the current findings contribute to a growing literature which suggests that mothers with HIV/AIDS may be particularly worried about their children learning of their illness likely due to the stigma associated with the disease, as well as the methods of transmission (e.g., Herek, 1999;Armistead et al, 2001;Kirshenbaum & Nevid, 2002). Consistent with the literature to date (e.g., Forsyth et al, 1996;Murphy et al, 2001;Shaffer et al, 2001), child knowledge of maternal HIV/AIDS was not consistently associated with better or worse outcomes for children in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with prior studies (Murphy et al, 1999;Armistead et al, 2001;Murphy et al, 2001), a relatively small number of children in the current analyses knew of their mother's HIV/AIDS. A mother's disclosure of any chronic or life-threatening illness to her child is often accompanied by some level of hesitation or worry regarding the child's reaction (Semple et al, 1993;Tompkins et al, 1999); however, the current findings contribute to a growing literature which suggests that mothers with HIV/AIDS may be particularly worried about their children learning of their illness likely due to the stigma associated with the disease, as well as the methods of transmission (e.g., Herek, 1999;Armistead et al, 2001;Kirshenbaum & Nevid, 2002). Consistent with the literature to date (e.g., Forsyth et al, 1996;Murphy et al, 2001;Shaffer et al, 2001), child knowledge of maternal HIV/AIDS was not consistently associated with better or worse outcomes for children in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A mother's disclosure of any chronic or life-threatening illness to her child is often accompanied by some level of hesitation or worry regarding the child's reaction (Semple et al, 1993;Tompkins, Henker, Whalen, Axelrod, & Comer, 1999). Mothers with HIV/AIDS may be particularly worried about their children learning of their illness given the stigma associated with the disease, as well as the methods of transmission (Herek, 1999;Armistead et al, 2001;Kirshenbaum & Nevid, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…32 However, child physical and behavioral problems, financial strains, and caregiving demands may leave little time for parental self-care. 29,31,[33][34][35] Among custodial, inner-city mothers with HIV, perceived parenting stress, more household members, and disclosure of HIV seropositivity to fewer family members predicted medication non-adherence and missed medical appointments. 29 However, little is known about whether parenthood, particularly custodial parenting, is associated with differential risk for conditions like depression, anxiety, substance use and abuse, or, conversely, increased positive states of mind or coping self-efficacy, among HIVϩ adults, especially since highly active antiretroviral therapy (HAART) has become widely available.…”
mentioning
confidence: 99%
“…Co-morbid conditions such as psychiatric illness and the subsequent use of psychotropic drugs may cause amenorrhea as well. HIV-seropositive women are exposed to multiple stressors (6), a phenomenon known to cause amenorrhea by increasing levels of corticotropin-releasing factor, which subsequently reduces gonadotropin-releasing hormone (7). The thrombocytopenia that is sometimes associated with HIV infection (8,9), or with some antiretroviral therapy such as Indinavir (10) may be associated with menorrhagia or metrorrhagia.…”
Section: Menstrual Disordersmentioning
confidence: 99%
“…HPV is clearly associated with HIV infection, but this association has been difficult to elucidate. Several longitudinal studies of HPV infection have demonstrated that HIV-infected women are more likely than HIV-negative women to have cervical HPV of all types: low risk types (6,11,26,40,53,54,55,66,83,84), medium risk types (33,35,39,51,52,56,58,59,68,73,82), and high risk types (16,18,31,45), more likely to have persistence of cervical HPV over time, and more likely to have a high viral signal of their HPV. Moreover HPV persistence is associated with CD4 counts <200 cells/µl, and the presence of HPV is associated with an increase in progression and decrease in regression (55,65,79,80).…”
Section: Lower Genital Tract Neoplasiasmentioning
confidence: 99%